Angiogenic Response to Major Lung Resection for Non-Small Cell Lung Cancer with Video-Assisted Thoracic Surgical and Open Access - Calvin S. H. Ng; Song Wan; Randolph H. L. Wong; Anthony M. H. Ho; Anthony P. C. Yim (The Scientific World Journal)
Background. Angiogenic factors following oncological surgery is important in tumor recurrence. Vascular endothelial growth factor (VEGF), angiopoietin 1 (Ang-1), Ang-2, soluble VEGF-receptor 1 (sVEGFR1) and sVEGFR2 may influence angiogenesis. This prospective study examined the influence of open and video-assisted thoracic surgery (VATS) lung resections for early stage non-small cell lung cancer (NSCLC) on postoperative circulating angiogenic factors. Methods. Forty-three consecutive patients underwent major lung resection through either VATS (𝑛=23) or Open thoracotomy (𝑛=20) over an 8-month period. Blood samples were collected preoperatively and postoperatively on days (POD) 1 and 3 for enzyme linked immunosorbent assay determination of angiogenic factors. Results. Patient demographics were comparable. For all patients undergoing major lung resection, postoperative Ang-1 and sVEGFR2 levels were significantly decreased, while Ang-2 and sVEGFR1 levels markedly increased. No significant peri-operative changes in VEGF levels were observed. Compared with open group, VATS had significantly lower plasma levels of VEGF (VATS 170±93 pg/mL; Open 486±641 pg/mL; 𝑃=0.04) and Ang-2 (VATS 2484±1119 pg/mL; Open 3379±1287 pg/mL; 𝑃=0.026) on POD3. Conclusions. Major lung resection for early stage NSCLC leads to a pro-angiogenic status, with increased Ang-2 and decreased Ang-1 productions. VATS is associated with an attenuated angiogenic response with lower circulating VEGF and Ang-2 levels compared with open. Such differences in angiogenic factors may be important in lung cancer biology and recurrence following surgery.